EP.TU.371The introduction of standardised ward round notes in the Acute Surgical Unit. (28th October 2021) - Johns, Jonathan; Rahman, Atiqur; Pearson, Katherine; Howse, Frances; Berry, David
Abstract: Introduction: A standardised approach to note-keeping has been shown to improve patient care and experience. Aims: This repeated audit cycle assesses the compliance with the introduction of a standardised proforma. Method: Data collection was prospective. Round 1 (n = 83) after introduction of a ward round proforma, Round 2 (n = 94) following result analysis / education, Round 3 (n = 62) following proforma changes. Results: (% Compliance with proforma) Conclusions: Some improvements were seen in Round 2. A notable improvement was observed in EDD and CFD when a tick box option was implemented in Round 3. Successful implementation of a standardised note-keeping requires repeated analysis, education and modification of the proforma.